2014
DOI: 10.4028/www.scientific.net/amm.633-634.451
|View full text |Cite
|
Sign up to set email alerts
|

Study on Properties of Ultrasonication Treated Pulp Fiber

Abstract: SEM and Automated Surface Area & Pore Size Analyzer were used to characterize surface morphology and specific surface area and the pore size distribution of fibers. The results showed that specific surface area and pore size distribution increase after ultrasonication. The ash content of the composites of ultrasonic treated fiber is larger than the untreated fiber, and the magnetic properties show a good superparamagnetic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…11,14 Ultrasonication can be regarded as a high energy treatment similar to PFI-refining but also leading to cavitation, resulting in more pronounced peeling and exposure of hydroxyl groups. 18,20,26 The combination of PFI-refining and subsequent ultrasonication might be a new approach to treat fibers for subsequent use in ductile applications, as the main toughening component in these new composites is the cellulose fibril, and not the fibers per se. A more severe degradation of the macroscopic structure may facilitate both the physical interaction with plasticizing additives and the covalent modification of the fibrous material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,14 Ultrasonication can be regarded as a high energy treatment similar to PFI-refining but also leading to cavitation, resulting in more pronounced peeling and exposure of hydroxyl groups. 18,20,26 The combination of PFI-refining and subsequent ultrasonication might be a new approach to treat fibers for subsequent use in ductile applications, as the main toughening component in these new composites is the cellulose fibril, and not the fibers per se. A more severe degradation of the macroscopic structure may facilitate both the physical interaction with plasticizing additives and the covalent modification of the fibrous material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The bleached chemical fibers were mixed with equal amounts of plasticizer and then suspended in water before being sonicated and subsequently dewatered to form papers, which to the best of our knowledge has not been reported in literature. Previous studies have shown that ultrasonication will fibrillate fibers and increase the specific surface area, which in turn might aid the sorption of plasticizers by increasing the availability of hydroxyl groups. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations